Penerapan Hukum Pidana terhadap Tindak Pidana dalam Pelayanan Angkutan Laut di Pelabuhan Bolok Kupang ditinjau dari Undang-Undang Nomor 17 Tahun 2008 tentang Pelayaran - Maria Phlisia Wulandari Modo; Heryanto Amalo; Darius Antonius Kian (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to determine the Conformity of the Application of Criminal Law at Bolok Port Kupang with Law Number 17 of 2008 concerning Shipping and inhibiting factors in the application of criminal law at Bolok Port Kupang. The type of research used is empirical legal research, the source and type of data in this study are primary data obtained from interviews at Bolok Port Kupang (PT. ASDP Kupang Branch) and secondary data were obtained from literature studies, then processed by examining and correcting and then analyzed in a qualitative descriptive manner. Based on the results of research and discussion, it can be concluded that: The application of criminal law Article 40, Article 41, Article 42, Article 132 of Law Number 17 of 2008 concerning Shipping at Bolok Port Kupang is not suitable because there is still an overload, insurance that only covers the occurrence of a ship accident that results in the death / injury of passengers but does not cover delays in loading passengers and delays in crossing, lack of facilities both on board and at the port and sailing carried out during bad weather resulting in the ship will return to port, which will greatly harm passengers because it interferes with the comfort and safety of passengers. The inhibiting factor so that the application of criminal law at Bolok Port Kupang has not been in accordance with Law Number 17 of 2008 concerning Shipping, namely public legal awareness, namely that there are still passengers who do not have tickets and many people often ignore their comfort to be able to board the ship which results in overloading. Lack of awareness of service providers such as not conducting counseling to (passengers), lack of facilities and no restrictions on ticket sales and information discrepancies.